REVOLUSI DIGITAL PAYMENT: ANALISIS FAKTOR PERSEPSI KEMUDAHAN, MANFAAT, DAN RISIKO TERHADAP MINAT GENERASI Z DALAM ADOPSI QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) - bukhori, reza fauzi (Program Studi Manajemen, Universitas Al Ghifari, 2025)
This study aims to analyze the influence of perceived ease of use, perceived usefulness, and perceived risk on Generation Z's interest in using the Indonesian Standard Quick Response Code (QRIS) as a digital payment method.The study used a quantitative approach with a survey method of 84 Generation Z respondents (born 1997-2012). Data were collected through a structured questionnaire and analyzed using multiple linear regression with SPSS 29.The results showed that: (1) Perceived ease of use had a positive and significant effect on interest in using QRIS (t-count = 3.546 t-table = 1.990, sig. 0.001); (2) Perceived usefulness did not have a significant effect on interest in using QRIS (t-count = 0.556 t-table = 1.990, sig. 0.579 0.05); (3) Perceived risk did not have a significant effect on interest in using QRIS (t-count = -0.449, sig. -0.654 0.05). Simultaneously, all three variables significantly influenced QRIS usage intention (F-count = 9.576 F-table = 3.11, sig. 0.001), contributing 26.4%.Gen Z prioritizes ease of use when adopting digital payment technology. Although perceived benefits and risks do not influence QRIS individually, the combination of these three factors collectively influences QRIS usage intention.